Integrated management model for the launch of a new product: 100% natural passion fruIt menthol candy - Ledesma Fernández, Javier D.; Correa Pérez, Jhon M. (Ingeniería Solidaria, 2012)
The authors of this research paper present, at first, the analysis of the company “Canutos” in order to clarify its outlook to embark on the production of a new product: 100% natural passion fruit menthol candy. Afterwards, they show the methodology applied in the development of an integrated management model with four fundamental aspects for the product launch: technical, legal, administrative and financial, which met the interests and expectations of the company when enacted. In this work, part of a graduation project for the industrial engineering program from the Universidad Pontificia Bolivariana (Medellin) entitled: “Integrated management model for the launch of a new product: 100% natural passion fruit menthol candy”, 2010, a systematic study was performed on Excel, it was then modeled with financial management tools for the information collected from the industry.
Keywords: passion fruit menthol candy; launch; integrated model